What Is the Value of an Address?. (May 2015) - Prescott, Charles
The history of street addressing and several different examples of valuing address systems are explored. The valuation calculations from the US, UK, Denmark and Costa Rica each have unique aspects. The fact that 'without an address you do not exist', and thus cannot participate fully in economic, political and civil society is noted and the consequences from several points of view explored. A recommendation to find new ways of valuing the address is put forward. Information is provided about a current Universal Postal Union competition in solving 'addressless situations' and participation is urged.